Where are the babies? Labor market conditions and fertility in Europe - Alicia Adsera (Institute for the Study of Labor (IZA), 2005)
Cross-country differences in both the age at first birth and fertility are substantial in Europe. The paper uses the European Community Household Panel 1994-2000 to investigate the relationship between unemployment of both women (and their spouses) with the timing and number of children. Maternity postponement is acute in countries with high and persistent unemployment since the mid 1980s. Moreover, the paper examines how fertility varies, for a similar level of unemployment, as a function of country-specific institutional arrangements. Wide access to part-time and to permanent positions (such as those in the public sector) is correlated with faster transitions to births. Short-term contracts are associated with delayed fertility instead.
Keywords: J13; J2; J6; H3; 330; fertility; unemployment; public sector; short-term contracts; maternity benefits